Communication Network Analysis in The Comment Section of A Youtube Podcast With AI - Sugianto, Larasati Indhita; Husain, A. Hasan Al (Bina Nusantara University, 2025)
The phenomenon of human-AI interaction is rapidly evolving, particularly in the realm of digital communication. One manifestation of this is the involvement of AI in YouTube content, such as podcasts that incorporate AI as a co-host. This study aims to analyze the comment network on the YouTube video â€œGua Podcast Bareng AI... Dia Manggil Gua Sayang... (Episode 1)â€ to understand user interaction patterns with AI in digital spaces. The research employs the Social Network Analysis (SNA) method, collecting comment data through YouTube digital tools and analyzing it using Gephi software. The findings reveal that interactions in the YouTube comment section form two primary communication patterns: the circular network and the Y network. The network structure consists of 2,313 nodes and 717 edges, with a modularity value of 0.86, indicating the formation of discussion clusters. The key actors in the network are @JoshRafG and @manueladrians, who exert the greatest influence based on centrality measures. Frequently occurring words in the comments include â€œAI,â€ â€œBisaâ€ (Can), â€œDanâ€ (And), and â€œManusiaâ€ (Human), reflecting discussions surrounding the pros and cons of AI as a communicative entity. This study reveals that AI in digital interactions is increasingly anthropomorphized, influencing users' perceptions of AI as a social subject. These findings contribute to digital communication studies, particularly in understanding AI's role in virtual interactions and shifting societal perceptions of artificial intelligence on social media.